Дихотомія свободи та рівності як детермінуюча засада права - Крисюк, Ю.; Krysiuk, Yu. (Волин. нац. ун-т. ім. Лесі Українки, 2020)
У статті досліджуються категорії свобода та рівність, їх спільності й відмінності, взаємозв’язок та взаємодія. Наголошується на тому, що свобода є передусім правом на нерівність, позаяк рівність завжди є посяганням на свободу. У дихотомії свободи та рівності ключову роль для суспільства відіграє третій елемент «конструкції права» – справедливість. Саме правова справедливість в кінцевому результаті є дотримання загального балансу, еквівалентності взаємних прав та обов’язків, якими пов’язані один з одним суб’єкти права. The article examines the categories of freedom and equality, their commonalities and differences, the relationship and interaction. The relationship between freedom and equality, given their functional contradictions, is a principal issue in the context of the fundamental values of social coexistence, in general, and law, in particular. It is emphasized that freedom is, first and foremost, a right to inequality since equality always contravenes freedom. In the dichotomy of freedom and equality, the third element of the ‘construction of law’, justice, plays a principal role in society. The legal justice ultimately means observance of the general balance, the equivalence of mutual rights and obligations, by which the subjects of law are connected with each other. Thus, freedom, equality, and justice form, as if the three vertices of the triangle that underlies the social institution of law. And none of them can be violated or restricted without detriment to the other two.
Freedom and Equality Dichotomy as a Determining Postulate of Law
Keywords: право; рівність; свобода; справедливість; суспільство; law; equality; justice; freedom; society; 340.12